Profiles of stress hormones in relation to DENV serotypes among dengue-positive patients - Misbah Anwar; Abdul Waheed; Tehseen Fatima; Sadaf Khan; Mariyam Shahzad; Talat Roome; Ibrar Ahmed; Seil Kim; Zohaib Ul Hassan; Muhammad Aurongzeb; Mohammed Saeed Quraishy; Salman Ahmed Khan (PLoS ONE, 2026)
Background Dengue, a mosquito-borne illness caused by the Flavivirus and second only to COVID-19 in global impact, affects over 112 countries. With four distinct serotypes, current research emphasizes understanding genetic diversity and improving treatment and diagnostics. This study explores the relationship between stress hormones (cortisol and adrenaline) and DENV-1 sequence homology in dengue-positive patients. Methods Among 165 subjects, hematological indices, NS1 antigen levels, and serotypes were analyzed. Hormone levels were quantified using ELISA, and viral load via RT-PCR. Amplicon sequencing and bioinformatics tools aided viral characterization. Statistical analyses included the Mann-Whitney U, Kruskal-Wallis, and Spearman’s correlation tests for non-parametric comparisons. Results The results revealed that cortisol and adrenaline levels were lower in dengue-positive patients, while patients infected with serotype DENV-2 showed comparatively higher epinephrine levels. DENV-1 was the most prevalent strain, accounting for 80% of cases. Hematological markers, including hemoglobin and red blood cell counts, showed comparable ranges. Phylogenetic reconstruction of DENV-1 whole-genome sequencing indicated multiple introductions into Pakistan from different countries, rather than a single source. The DENV-1 strain was found to predominantly affect males in Karachi. Notably, comparisons across different DENV serotypes did not reveal statistically significant differences in stress hormone response, indicating only descriptive trends. Spearman’s correlation analysis showed weak, non-significant associations between viral load and cortisol (r = 0.184, p = 0.170) and between viral load and epinephrine (r = 0.165, p = 0.224). Statistically significant but negative correlation was observed only between viral load and hemoglobin (r = −0.228, p = 0.005). Conclusion These findings enhance our understanding of the complex interactions between dengue serotypes and their impact on infection progression, particularly in relation to stress hormones and viral load. However, as most associations were exploratory and not statistically significant. The descriptive trends identified here highlight the need for larger, longitudinal studies to better define the relationship between stress hormones, viral load, and dengue severity.